Sociodemographic characteristics, dietary intake, and body image dissatisfaction among Saudi adolescent girls - Bahathig, Abeer Ahmad; Abu Saad, Hazizi; Md Yusop, Nor Baizura; Mohd Sukri, Nurul Husna; El-Din, Maha M. Essam (Universiti Putra Malaysia, 2023)
This study assesses sociodemographic characteristics, dietary intake and body image dissatisfaction (BID) among Saudi adolescent girls. A total of 399 girls ages 13-14 were randomly selected from intermediate schools in Arar, Saudi Arabia. Data on anthropometric measurements, sociodemographic characteristics, dietary intake and body image (BI) were collected. Multiple linear regression was used to predict the association between variables. Most adolescents had a normal weight based on their body mass index (BMI), normal waist circumference (WC), and normal waist-to-height ratio (WHtR). Fried chicken and Kabsa rice were the most frequently consumed foods; most girls consumed excessive fat. Most girls had BID (81.5), and 51.4 desired to lose weight. BMI was positively correlated with age and current BI (p<0.001) and negatively associated with dairy product intake (p=0.004) and desired BI (p<0.001). WC had a positive association with age (p=0.001) and current BI (p<0.001) and a negative association with dairy product intake, cereal and grain intake (p=0.001) and ideal BI (p<0.001). WHtR was positively associated with current BI (p<0.001) and negatively associated with cereal and grain intake (p=0.005), dairy product intake and desired BI (p<0.001). Although most participants had a normal weight, they consumed excessive fat and were dissatisfied with their BI, which are significant predictors of obesity. Saudi adolescent girls require nutritional interventions to help them transition to a healthy diet, positive BI and healthy lifestyle.